The study of the communication of intellectual capital - Wee, Janet Chui Neo (2017)
The study examines the communication of intellectual capital (CIC), defined as information disclosure of an organization’s intangible assets through annual report and supplementary corporate disclosure (ARS). Three research gaps were identified: (1) There is insufficient understanding of the drivers behind corporate disclosure of IC in the ARS; (2) How IC is communicated for corporate reporting, particularly content and formats used; and (3) The relationship between CIC and organizational performance (OP) has not been established.